Cyberslacking and Academic Procrastination Among Studens: The Moderating Role Of Gender - Rinaldi, Martaria Rizky; Damayanti, Lalita Dewi (IDEA: Jurnal Psikologi, 2025)
College students face high academic and social demands, putting them at risk of engaging in academic procrastination. Procrastination is known to be related to cyberslacking, while gender is identified as a variable influencing how individuals interact with technology and respond to academic demands. This research aims to explore the relationship between cyberslacking and academic procrastination, with gender as a moderating factor among college students. The study employs a quantitative correlational approach with demographic data and two scales: the Cyberslacking Scale and the Academic Procrastination Scale. The research participants consist of 247 students aged 18 to 25. Data analysis includes descriptive analysis and moderation analysis using Jamovi software. The results show no direct significant relationship between cyberslacking and academic procrastination. Although gender significantly influences procrastination, the interaction between cyberslacking and gender is not significant, indicating a uniform impact across genders. The findings of this study can contribute to the development of interventions or educational programs to address challenges among college students.